2017
DOI: 10.5751/es-09130-220142
|View full text |Cite
|
Sign up to set email alerts
|

Social-ecological traps hinder rural development in southwestern Madagascar

Abstract: ABSTRACT. The semiarid Mahafaly region in southwestern Madagascar is not only a unique biodiversity hotspot, but also one of the poorest regions in the world. Crop failures occur frequently, and despite a great number of rural development programs, no effective progress in terms of improved yields, agricultural income, or well-being among farming households has been observed. In addition to the severe development challenges in the region, environmental degradation and the loss of biodiversity are prevailing is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…The dependence has grown over time through interactions in opportunities, capacities, and motivations to fish, and these interactions made the trap progressively more difficult to escape. The shrinking potential to change the situation indicates rigidity, which is a common feature of SE traps in general (Scheffer and Westley 2007, Cumming 2018, Haider et al 2018 and of SE traps in the fisheries context (Steneck et al 2011, Laborde et al 2016, Hanh and Boonstra 2018. In what follows, we first elaborate on the possibilities to escape the trap and then suggest a management strategy to avoid this situation in other place-based fisheries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dependence has grown over time through interactions in opportunities, capacities, and motivations to fish, and these interactions made the trap progressively more difficult to escape. The shrinking potential to change the situation indicates rigidity, which is a common feature of SE traps in general (Scheffer and Westley 2007, Cumming 2018, Haider et al 2018 and of SE traps in the fisheries context (Steneck et al 2011, Laborde et al 2016, Hanh and Boonstra 2018. In what follows, we first elaborate on the possibilities to escape the trap and then suggest a management strategy to avoid this situation in other place-based fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently suggested that place-based fishers and other placebased resource users tend to use resources sustainably (e.g., McGoodwin 1990, Masterson 2016. However, in cases where opportunities to diversify income activities or access to other resources are limited, bonds to a specific place may represent a barrier for sustainable resource use (Hanh and Boonstra 2018). Second, Swedish eel fisheries represent a relatively small part of the total anthropogenic pressure to which the eel is exposed (Dekker et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causal loop diagrams are tools used to represent interactions among system entities and how entities and interactions are affected by external factors [9,26]. In regard to rigidity traps, causal loop diagrams may be particularly useful for identifying social-ecological feedbacks that encourage and discourage rigidity traps, as well as the influences of different forms of context (e.g., spatial, historical, and socioeconomic) on rigidity traps and feedbacks.…”
Section: Causal Loop Diagrammingmentioning
confidence: 99%
“…Causal loop diagram A tool for visualizing relationships among system variables and external factors [9].…”
Section: Trap Type Definitionmentioning
confidence: 99%